OHP-046 Serious adverse drug events: the role of the hospital pharmacist in Campania Region's emergency department. (24th February 2014) - Ruggiero, F; Taurasi, F; Aliberti, FA; Micera, D; Melillo, A; Russo, L
Abstract : Background: Serious adverse events from the treatment (adverse drug events, ADE) are among the leading causes of hospitalisation and patient death. The work of hospital pharmacists in emergency departments has been essential in focusing the attention of the scientific community on ADEs of particular clinical relevance. Purpose: To improve a pharmacovigilance system that could, for example, reveal the incidence of severe ADEs in the population. Materials and methods: The pharmacovigilance activities in three Campania hospitals (Avellino, Benevento, Salerno in their emergency departments (First Aid, Emergency Medicine), revealed a significant increase in reports of ADEs, especially those classified as 'serious'. Results: Of 656 reported ADEs, 249 (38%) were considered to be 'severe' compared to only 5 'severe' reports included in the previous two years. In particular, data related as 'serious' reactions show 233 cases of hospitalisation /hospital prolongation, 15 life-threatening and 1 death; 130 cases of females, 119 males, also the number of adults aged 18–55 (125) is greater than both patients over 55 (121) and is (significantly) greater than the number of paediatric patients (3). Finally, the active ingredients involved the most were acetylsalicylic acid (30) and warfarin (22) while there have been several cases related to antibiotics such as amoxicillin/clavulanic acid (19) and ceftriaxone (18). The System Organ Class classification shows that the reported serious events concerned above all gastrointestinal disorders (208), skin and subcutaneous tissue diseases (162), systemic diseases and conditions related to the administration site (63). Conclusions: A hospital pharmacist in the emergency departments has encouraged the unit's staff to get involved in pharmacovigilance activities. The attention given to cases defined as 'serious, ' underlined how these may have an effect in clinical, economic and public health terms as their evaluation may influence different levels of decision-making. No conflict of interest.